Proteome profiling of endogenous and potential S-nitrosylation in colorectal cancer - Liang, Feng; Wang, Shuang; Guo, Yu; Mu, Yu; Shang, FengJia; Wang, Min (Frontiers in Endocrinology, 2023)
Background. As a common cancer with high incidence rate and mortality, colorectal cancer (CRC) is seriously threatening human health. S-nitrosylation (SNO) proteins mediated by nitric oxide (NO) has important implications in the genesis, progression, and apoptosis of CRC. It’s worth noting that the SNO proteins also play an important role in the tumor endocrine and metabolic pathways of CRC. Materials and methods. In this study, the protein extracts of human tissues and cell lines were treated by biotin switch technology and magnetic beads enrichment. The proteomic results of endogenous and potential SNO proteins were analyzed by mass spectrometry (MS). Through the comparison and analysis of MS results, Gene Ontology (GO) analysis, and literatures, some endogenous and potential SNO proteins were identified in CRC, which were closely related to the tumor endocrine and metabolic pathways, the apoptotic signaling pathways, protein maturation, and other biological processes of the proliferation and apoptosis of CRC cells. Results. A total of 19 proteins containing potential or endogenous SNO sites were detected in both human cancer tissue and SW 480 cells. Through the cross validation of MS results, GO analysis, and literatures, several SNO proteins were identified frequently in CRC, such as the actin, cytoplasmic 1 (ACTB), peroxiredoxin-4 (PRDX4), protein S100A8 (S100A8), pyruvate kinase PKM (PKM), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which were closely related to the tumor endocrine and metabolic pathways and the apoptotic signaling pathways of CRC. Conclusion. Different CRC cells and tissues contained potential and endogenous SNO modified proteins. In addition, some SNO proteins could participate in the proliferation, metastasis and apoptosis of CRC by regulating the tumor endocrine and metabolic pathways.